PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN BERBASIS NILAI KEADILAN - Radi Yusuf (Jurnal Pembaharuan Hukum, 2014)
Divorce is a part of the marriage, because there would be no divorce without any prior marriage. If in divorce there is a dispute on the division of joint property, the settlement of disputes concerning joint property may be filed through the Religious Court, as the provisions of Article 88 Compilation of Islamic Law. This research method using normative juridical approach, ie anapproach to legislation that analyze a rule used to determine the division of joint property due to divorce. The results obtained showed: 1) That the factors that influence the decision of courts that do not deliver justice is Factor Substance Law, Legal Structure Factor, Factor Culture Law. 2) Implications of the implementation of the division of joint property due to divorce based onvalues of justice resulted in a) Changes in the division of joint property paradigm concept of divorce is the judge as law practitioners, will be transformed into the figure of the judge as the law enforcement and justice. b) Changes in the model along with the division of property due to divorce, namely treasure together divided in accordance with the provisions of Article 97Compilation of Islamic Law and treasure together divided not in accordance with the provisions of Article 97 Compilation of Islamic Law, division of such assets based on sources giving a living.